"Land rights in India: policies, movements and challenges/ edited by Varsha Bhagat-Ganguly" (Routledge, 2016)
This volume engages with the topical issue of land rights in neoliberal India. It examines government policies, laws, land governance and land reforms from the perspective of social justice and people$1 (Bs response to dispossession of land. Looking beyond the dominant discourse of land acquisition and the conception of land as a commodity for economic growth, the book explores critical themes including issues of social identity, culture, livelihood and food security through a study of land reform; reviews existing land policies and legal dimensions; and discusses issues and challenges of land governance and land dependents as well as perspectives from people$1 (Bs movements. Lucidly written, based on empirical research, and comprehensive in its treatment of a contentious concern, this volume will be useful to scholars and researchers of economics and public policy, development studies, political science, and political economy. It will also interest scholars of South Asian studies and sociology.s
Keywords: Land rights -India